(untitled) (Bangladesh Journal of Livestock Research, 2021)
The purpose of the experiment was to investigate the litter size and growth performance of four distinct crossbred sheep at Bangladesh Livestock Research Institute (BLRI). Data were obtained on 160 crossbred sheep of Dorper, Perendale, Suffolk, and Damara raised on BLRI sheep research farm, Savar, Dhaka, from January 2021 to June 2022. The effects of genotype, sex, and season on birth weight (Bwt), 3 months body weight (Bwt3m), 6 months body weight (Bwt6m), 12 months body weight (Bwt12m), average daily gain from birth to 3 month (ADG3m), 3 to 6 month (ADG6m), and 6 to 12 month (ADG12m) of ages and litter size (LS) of doe were investigated. All the data in this study were analyzed by the Statistical Package for the Social Sciences (SPSS) version 20.0 computer program and the significance differences among the mean values were ascertained using Duncan’s multiple range test (DMRT). The effect of genotype on Bwt6m was found highly significant p<0.01). Genotype had also a significant (p<0.05) effect on Bwt3m, ADG3m, and ADG6m. The effect of season was found to be insignificant (p>0.05) except for Bwt3m and ADG3m ((p<0.05). Among the four crossbred genotypes, the highest litter size was found in Damara crossbreds (1.44±0.07) while, the highest birth weight was found in Dorper crossbreds (2.09±0.05 kg), and the highest body weight at 12 months of ages was found in Suffolk crossbreds (20.58±1.33 kg). The growth performance and litter size of BLRI developed four different crossbred sheep may be improved by proper breeding, nutrition, health, and other management. Bang. J. Livs. Res. Vol. 28 (1&2), 2021: P. 42-49